The effects of project manager’s soft skills on success of the project in the Malaysian construction industry - Wen, Bao Jun (2023)
This study is aimed to explore the effectiveness of soft skills (SK) in the Malaysia construction industry (CI) and the objectives of this study are threefold. The first is to identify the scope of soft skills required in the Malaysian construction industry, the second is to examine the awareness of soft skills among Malaysian construction industry practitioners and to investigate the impact of soft skills on project managers in contributing to project success, and the third is to assess the most effective methods of acquiring and improving soft skills. To obtain accurate findings, Specific 200 questionnaires were distributed to project managers in the Malaysian construction industry practitioners within Kuala Lumpur, Klang, Johor Bahru regions, and the data collected was analysed through Statistical Package for Social Science (SPSS) analysis software. Cronbach's Alpha reliability test was used for examining the internal consistency and the mean was used for assessing the effectiveness of the SK. The findings show that effective communication, teamwork, and trust building were identified as the most significant soft skills; The three most effective soft skills are effective communication, resolving conflict and crisis, and personal attitude. The most effective methods of acquiring and improving soft skills are self-development, peer development, and coaching and Mentoring. These findings identifying the most effective soft skills and ways to acquire and improve them will contribute to the construction practitioners improving SK level and project performance, thereby reducing the risk of project failure due to cost and time overruns. As well as the study enriches the Malaysian soft skills system and will be useful for future investigations.